Biochar based sorptive remediation of steroidal estrogen contaminated aqueous systems: A critical review - Peiris, Chathuri; Nawalage, Samadhi; Wewalwela, Jayani J.; Gunatilake, Sameera R.; Vithanage, Meththika (My University, 2020)
Remediation of steroidal estrogens from aqueous ecosystems is of prevailing concern due to their potential impact on organisms even at trace concentrations. Biochar (BC) is capable of estrogen removal due to its rich porosity and surface functionality. The presented review emphasizes on the adsorption mechanisms, isotherms, kinetics, ionic strength and the effect of matrix components associated with the removal of steroidal estrogens. The dominant sorption mechanisms reported for estrogen were π–π electron donor-acceptor interactions and hydrogen bonding. Natural organic matter and ionic species were seen to influence the hydrophobicity of the estrogen in multiple ways. Zinc activation and magnetization of the BC increased the surface area and surface functionalities leading to high adsorption capacities. The contribution by persistent free radicals and the arene network of BC have promoted the catalytic degradation of adsorbates via electron transfer mechanisms. The presence of surface functional groups and the redox activity of BC facilitates the bacterial degradation of es trogens. The sorptive removal of estrogens from aqueous systems has been minimally reviewed as a part of a collective evaluation of micropollutants. However, to the best of our knowledge, a critique focusing specifically and comprehensively on BC-based removal of steroidal estrogens does not exist. The presented review is a critical assessment of the existing literature on BC based steroidal estrogen adsorption and attempts to converge the scattered knowledge regarding its mechanistic interpretations. Sorption studies using natural water matrices containing residue level concentrations, and dynamic sorption experiments can be identified as future research directions.
Keywords: Steroidal estrogens; Biochar; Endocrine disrupting chemicals; Sorptive removal